Expanding Health Care Provision in a Low-Income Country : The Experience of Malawi - Chansa, Collins; Pattnaik, Anooj (World Bank, Washington, DC, 2018)
Malawi is a low-income country that is actively working toward achieving universal health coverage (UHC). The government is committed to provide adequate health care, commensurate with the health needs of Malawian society, and international standards of health care as outlined in the Constitution. This UNICO case study explores how Malawi has been able to increase population coverage and financial protection by implementing these two supply-side reforms. The study reviews the situation before the two reforms, what the two reforms envisioned, management arrangements, what the reforms delivered (including positive and negative effects), and the long-term scope for achieving UHC in Malawi.